Potential Utilization of Rice Waste in the Construction Sector: A Multi-Criteria Decision Analysis Approach (2024)
Effective management of agricultural waste is an important contribution to environmental sustainability and economic development, especially considering the significant volume of agricultural residues produced worldwide. Rice is a widely cultivated crop in Colombia, and its high production results in a high amount of wastes, which is often underutilized due to a lack of knowledge regarding its potential value-added applications. On the other hand, the construction industry has become increasingly aware of the necessity to develop materials with reduced environmental impact. Therefore, this study explores the application of the Analytic Hierarchy Process (AHP) to evaluate various alternatives for utilizing rice waste in construction materials; the alternatives were evaluated based on criteria tailored to the needs of local agricultural communities in the Tolima region of Colombia. The findings highlight the potential of rice husk ash (RHA) as an environmentally responsible alternative in the construction sector, offering a viable solution for waste management while contributing to the economic development of small-scale farmers.